DYNAMICS, STRUCTURE AND DRIVERS OF FISH CATCH IN RUSSIAN FEDERATION (2005–2017) - V. V. Samoylenko (Известия ТИНРО)
The main trends in fisheries are considered by the fishery basins, including dynamics of annual catches and changes in their structure, both for inland and marine areas, on the data of fishery statistics for 2005–2017. The landing in the inland waters of Russian Federation is estimated as 8.4–10.0 % of the total national annual catch. Its mean annual volume for this period was 375.103 t; it grew on average in 2.2 % annually. This volume was landed mainly (85 %) in four inland basins: Volga-Caspian, Far Eastern, Azov-Black Sea, and West Siberian ones. About ⅓ of the volume was provided by cultivated fish, in particular in the Azov-Black Sea basin (87 % of the total freshwater catch) and Northern basin (69 %). Marine fishery produced 2990–4644 . 103 t, or 90.0–91.6 % of the total Russian catch. Its annual landing has increased by more than a half since 2005, with the average growth in 3.7 % annually. This volume was landed mainly within the exclusive economic zone (EEZ) of Russia — 74.7 %, the rest was landed in the neutral areas of the World Ocean (5.9 %) or in EEZ of foreign states (19.4 %). The main region of marine fishery is the Far-Eastern basin, which portion in the national catch increased in 13 years from 62.6 % to 68.7 %, whereas the portion of the Northern and Western basins decreased in 3.7 % (to 21.5 %) and 3.0 % (to 7.9 %), respectively. In the Far-Eastern basin almost whole catch was landed within EEZ of Russia (3149 . 103 t), though in the Northern and Western basins the catch was obtained mainly in EEZ of foreign states (on average 557 . 103 t and . 103 t, respectively) and beyond EEZ (116 . 103 t and 94 . 103 t, respectively). Influence of the export supplies on the fish supply to the domestic market of Russia is analyzed. The landings increase contributes to the export increasing, but other factors are likely to be the main drivers of the export growth. This information on quantitative structure of the national annual catch could be used in economical forecasts and for developing of programs and strategies for the fishery industry of Russia. Examples of its practical using for solving of some applied problems in the economics are presented.